Prediction Of Uncontrolled Dyslipidemia Of Cardiac Outpatients And The Adverse Effect Of Pharmaceutical Excipients - Abdulrazzaq, Hadeer Akram (2013)
Uncontrolled dyslipidemia is still a difficult problem to be achieved during therapy of cardiac patients. Several authors stated contribution of patients’ adherence, physicians’ practice and active ingredients to attain goals of dyslipidemia control, but none combined all these causes. Unfortunately few studies discussed the effects of pharmaceutical excipients in clinical practice and especially dyslipidemia. Objectives of this study were to determine predictors of uncontrolled dyslipidemia, poor lipid profile, adverse drug reactions (ADRs), and effects of pharmaceutical excipients. Second is implementation of an intervention tool to improve the knowledge of healthcare professionals about pharmaceutical excipients. First objective was carried out at Cardiac Clinic of Hospital Pulau Pinang in Malaysia, while the second was conducted at Hospital Pulau Pinang (Malaysia) and Al-Kadhimiya Teaching Hospital (Iraq). Dyslipidemia control and lipid profile were evaluated depending on the National Cholesterol Education Program (NCEP) guideline. Validated questionnaires were filled by patients to determine their adherence and common ADRs during therapy. Healthcare professionals answered validated questionnaires; one for physicians to determine their practice for dyslipidemia control, and another to assess their knowledge about pharmaceutical excipients. Other information like patients’ characteristics, concurrent medications, diseases, and lipid profile were collected from patients’ progress files.